Cystic Fibrosis: Is it Extremely Rare or Invariably Missed? An Observational Study in Bangladesh Scenario (Global Journal of Medical Research, 1970)
Cystic fibrosis CF the most common genetic disorder among the Caucasian population was believed to be extremely rare or non-existent in Indian subcontinent countries like Bangladesh But the real scenario is not so infrequent as per belief
Keywords: cystic fibrosis; sweat chloride; pilocarpine iontophoresis; bangladesh